Exploring the experiences of an exercise-based telerehabilitation program among Canadian community-dwelling adults with stroke - Wiley, Elise; Sakakibara, Brodie; Park, Sarah; Barclay, Ruth; Bayley, Mark; Eng, Janice J; Harris, Anne; Inness, Elizabeth; MacKay-Lyons, Marilyn; MacDermid, Joy; Pollock, Courtney; Pooyania, Sepideh; et al. (Taylor & Francis, 2024)
Purpose: Telerehabilitation is emerging as a means for delivering stroke rehabilitation to address unmet lower extremity rehabilitation needs. However, there is currently limited and low-quality evidence supporting the use telerehabilitation interventions for lower extremity recovery after stroke. Thus, we developed an exercise-based telerehabilitation program (TRAIL) for safe and effective promotion of lower extremity function after stroke. This study reports on the qualitative findings from the feasibility study of the TRAIL program. Methods: An interpretive description methodology and inductive thematic analysis approach were undertaken. One-on-one semi-structured interviews were conducted on a subset of participants who completed the TRAIL feasibility study. Participants were recruited via email and enrolled into the study based on pre-determined purposeful sampling strategies. Results: Ten participants (6 men, 4 women) completed a semi-structured interview. Two main themes emerged: (i) TRAIL ingredients for success and (ii) telerehabilitation is a viable option for stroke rehabilitation. Conclusion: Exercise-based telerehabilitation appears to be well-received by men and women post-stroke when social support, professional guidance, and program resources are offered. TRAIL may also prolong the continuum of care that individuals receive once they are discharged back into the community, and contribute to improvements in mobility, lower extremity strength and balance.
Keywords: Telerehabilitation; Exercise; Stroke; Virtual rehabilitation; Qualitative